CONCEPTS AND SYMBOLS DEFINING NAFS - Almardonova Aziza is the daughter of Almamat (American Journals Publishing, 2025)
In this study, the concepts of the self found in the works of our classical literature were sorted out. The article provides specific information about symbols related to lust. The embodiment of the concept of soul in the image of various animals is studied on the basis of poetic verses. In the study, using statistical, comparative-typological methods, the manifestations of classical works related to the concept of self were analyzed. Symbols representing lust are classified separately.
Keywords: Nafs, woman, bird, parrot, ostrich, lion, wild bird, carcass bird, world.